2023
DOI: 10.1002/fes3.462
|View full text |Cite
|
Sign up to set email alerts
|

Resources for plant‐based food: Estimating resource use to meet the requirements of urban and peri‐urban diets

Abstract: The rapid urban growth seen globally in recent years has not been supported by a simultaneous increase in agricultural land and/or crop productivity. Producing crops in (peri‐)urban areas shows good potential to provide the vegetable products for a healthy and balanced diet for the growing population, but it has to deal with the local availability of resources. Thus, meeting the food requirements of the urban population as efficiently and robustly as possible is a challenge. This study developed a methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…A rough estimate for the highest possible WUE in this case can be made by considering that vegetable crops are mostly water, and that this is true for all plant parts. In this case, the highest possible WUE would be equal to the crop's harvest index -the ratio of harvestable plant parts, relative to the total plant weight ( [33], [65]). This is equivalent to a potential WUE of 500-800 gr litre -1 for a tomato crop [66], and some 850 gr litre -1 for a lettuce crop (e.g., [21]).…”
Section: High Water Use Efficiency and Reduced Emissions Require [Muc...mentioning
confidence: 99%
See 1 more Smart Citation
“…A rough estimate for the highest possible WUE in this case can be made by considering that vegetable crops are mostly water, and that this is true for all plant parts. In this case, the highest possible WUE would be equal to the crop's harvest index -the ratio of harvestable plant parts, relative to the total plant weight ( [33], [65]). This is equivalent to a potential WUE of 500-800 gr litre -1 for a tomato crop [66], and some 850 gr litre -1 for a lettuce crop (e.g., [21]).…”
Section: High Water Use Efficiency and Reduced Emissions Require [Muc...mentioning
confidence: 99%
“…Indeed, in such a tomato greenhouse in Saudi Arabia, Tsafaras et al [65] reported a water use efficiency of 500 gr litre -1 . Righini et al ( [33],…”
Section: High Water Use Efficiency and Reduced Emissions Require [Muc...mentioning
confidence: 99%